A molecular case-control study of the Merkel cell polyomavirus in colon cancer. - Campello, Cesare; Comar, Manola; D'Agaro, Pierlanfranco; Minicozzi, Anna; Rodella, Luca; Poli, Albino (J Med Virol, 2011)
To explore the putative role of the Merkel cell polyomavirus in human colon cancer, a prospective molecular case-control study was undertaken in patients and their relatives enrolled during a screening program. Fresh tissue samples from 64 cases of colon cancer (mean age 69.9 ± 11.0 years; 40 males) and fresh biopsies from 80 relatives (mean age 53.7 ± 8.6 years; 43 male; 55 son/daughter, 23 brother/sister, 2 parents) were analyzed by PCR and sequencing. Pre-cancerous lesions, namely adenomas and polyps, were detected in 15 (18.8%) and 9 (11.2%) of the controls, respectively. In addition, 144 blood samples were examined. Merkel cell polyomavirus DNA was detected in 6.3% of cases and 8.8% of controls. This difference was not statistically significant in the logistic regression analysis, after adjustment for age. Whereas blood samples from both cases and controls tested negative, the DNA Merkel cell polyomavirus was identified in 12.5% of adenoma/polyp tissues. No statistically significant difference was found when prevalence rates of Merkel cell polyomavirus in normal, pre-cancerous and cancer tissues were compared. Sequence analysis of the viral LT3 and VP1 regions showed high homology (>99%) with those of strains circulating worldwide, especially with genotypes detected in France. The findings of this survey are consistent with the hypothesis that the Merkel cell polyomavirus, in addition to other human polyomaviruses, can be recovered frequently from the gastrointestinal tract, because it is transmitted throughout the fecal-oral route. Moreover, the study does not indicate a role for Merkel cell polyomavirus in the genesis of colon cancer.
Keywords: Aged; Aged, 80 and over; Case-Control Studies; Cluster Analysis; Colonic Neoplasms; DNA, Viral; Female; Genotype; Humans; Italy; Male; Merkel Cells; Middle Aged; Molecular Sequence Data; Polymerase Chain Reaction; Polyomavirus; Polyomavirus Infections; Prevalence; Sequence Analysis, DNA; Tumor Virus Infections

Corticosteroids do not cause harmful increase of viral load in severe H1N1 virus infection. - Confalonieri, Marco; D'Agaro, Pierlanfranco; Campello, Cesare (Intensive Care Med, 2010)
Keywords: Adult; Antiviral Agents; Bronchoalveolar Lavage Fluid; Extracorporeal Membrane Oxygenation; Glucocorticoids; Humans; Influenza A Virus, H1N1 Subtype; Influenza, Human; Male; Methylprednisolone; Oseltamivir; Respiration, Artificial; Severity of Illness Index; Viral Load; World Health Organization

Detection of SV40 in colon cancer: a molecular case-control study from northeast Italy. - Campello, Cesare; Comar, Manola; Zanotta, Nunzia; Minicozzi, Anna; Rodella, Luca; Poli, Albino (J Med Virol, 2010)
To explore the involvement of the simian polyomavirus SV40 in human colon cancer, a molecular case-control study was undertaken in patients and in their relatives living in an area where the spread of SV40 has already been documented. From 2006 to 2008, 94 colon cancer patients (age: 37-90 years) and 91 subjects (age: 32-70 years) relatives of each index case were enrolled. A blood sample and a specimen of cancer tissue or biopsy were collected, from each patient or control, respectively. Samples were analyzed twice for Polyomavirus (i.e., SV40, JCV, and BKV) by PCR and by quantitative real-time PCR (RT-qPCR) with reproducible results. No BKV/JCV was detected either in normal or pathological tissues. SV40 was not present in control subjects, either normal tissue or in biopsies from adenomas or polyps. All blood samples were negative. Conversely, six adenocarcinoma specimens were positive for SV40 sequences (overall prevalence 6.4%, P = 0.03 in comparison with controls). Nevertheless, the SV40-associated colon cancer risk proved statistically not significant (OR = 3.91; P = 0.115) when adjusted for age. Quantitation of SV40 DNA performed by RT-qPCR showed a low viral load ranging from 6.2 x 10(1) to 9 x 10(3) copies per reaction. This molecular case-control survey showed, for the first time in fresh samples and by RT-qPCR, that SV40 can be detected in colon cancer tissue. However, the finding was not statistically significant when compared with a well-structured community control group. Thus, the role of SV40 and other polyomavirus in colon cancer genesis deserves further investigation.
Keywords: Adenocarcinoma; Adult; Aged; Aged, 80 and over; BK Virus; Case-Control Studies; Colonic Neoplasms; DNA, Viral; Female; Humans; Italy; JC Virus; Male; Middle Aged; Polymerase Chain Reaction; Polyomavirus Infections; Simian virus 40; Tumor Virus Infections

Epidemiological and molecular assessment of a rubella outbreak in North-Eastern Italy. - D'Agaro, Pierlanfranco; Dal Molin, Gianna; Zamparo, Emanuela; Rossi, Tatiana; Micuzzo, Michele; Busetti, Marina; Santon, Daniela; Campello, Cesare (J Med Virol, 2010)
From January to June 2008, a rubella outbreak involving 111 laboratory confirmed cases occurred in the Friuli Venezia Giulia (FVG) region of North-Eastern Italy. The outbreak occurred initially in two residential homes for young adults disabled mentally and physically. Subsequently, the epidemic spread to the general population. Young adult cohorts were mostly affected and the mean age of the patients was 26.8 years; the majority of cases were male (73.8%), with a mean age of 26.6 years in males and 27.4 in females. Three pregnant women had a primary infection and two had their pregnancies terminated. Genotyping of 16 isolates showed the circulation of RUBV 2B, a genotype originating from Asia and South Africa and now present in Europe. In addition, molecular analysis revealed a well defined space-temporal spread of two viruses showing distinct sequences. A seroepidemiological survey carried out in a city within the same geographical area showed that the proportion of women of childbearing age still susceptible to rubella virus was 5.5%, fairly close to the figure (<5%) expected by 2010.
Keywords: Adolescent; Adult; Antibodies, Viral; Disease Outbreaks; Epidemics; Female; Genotype; Humans; Immunoglobulin G; Italy; Male; Pregnancy; Pregnancy Complications, Infectious; Rubella; Rubella virus; Young Adult

HLA-G*0105N allele is associated with augmented risk for HIV infection in white female patients. - Segat, Ludovica; Catamo, Eulalia; Fabris, Annalisa; Morgutti, Marcello; D'Agaro, Pierlanfranco; Campello, Cesare; Crovella, Sergio (AIDS, 2010)
We analyzed HLA-G 3777G > C, HLA-G 14 bp deletion/insertion and HLA-G*0105N polymorphisms in HIV-positive white adult participants, infected through horizontal heterosexual transmission, and unexposed uninfected individuals, all from north eastern Italy. We report a new association between the HLA-G*0105N allele and HIV infection in adult white female participants, being HLA-G*0105N null allele correlated with an augmented risk (odds ratio = 4.35, 95% confidence interval = 1.38-18.07, P = 0.005) for HIV infection.
Keywords: Adolescent; Adult; Aged; Female; Genetic Predisposition to Disease; Histocompatibility Antigens Class I; HIV Infections; HIV-1; Humans; Middle Aged; Polymorphism, Genetic; Young Adult

JCV/BKV and SV40 viral load in lymphoid tissues of young immunocompetent children from an area of north-east Italy. - Comar, Manola; Zanotta, Nunzia; Bovenzi, Massimo; Campello, Cesare (J Med Virol, 2010)
Polyomavirus infection occurring during childhood is followed by a lifelong latency in immunocompetent subjects. The major site of polyomavirus persistence are the uroepithelial cells which leads to oral transmission. It has recently been hypothesized that tonsils could be a possible reservoir. The role of tonsil, adenoid, and peripheral blood mononuclear cells (PBMCs) as possible sites of JCV, BKV, and SV40 latency in young healthy children was assessed. Two hundred fifteen fresh specimens, including 57 tonsil, 80 adenoid, and 78 PBMC samples from 80 immunocompetent children (mean age 4.8 years) were analyzed to determine the viral load by quantitative real-time PCR. The human herpes virus 6 (HHV-6) was tested as a lymphotropic reference virus. Polyomavirus was detected in 5/80 (6.2%) children while HHV-6 infection affected 27/80 children (33.7%) (P < 0.001). SV40 was detected in one adenoid sample, while footprints of BKV were found in one adenoid and three tonsil samples. JCV was never found in all samples. Polyomavirus sequences were not detected in the 78 blood samples. One adenoid and two tonsils from three children (1.4%) were positive for both polyomavirus and HHV-6. Infections were characterized by low replication rates ranging typically from 1 x 10e(2)/5.5 x 10e(4) to 6.8 x 10e(3)/8.5 x 10e(4) viral copies/number of cells. In conclusion, tonsils and adenoids of children could effectively harbor BKV and SV40, although only very few cells proved to be infected. Nevertheless, the low prevalence of polyomavirus, in comparison with the lymphotropic HHV-6, suggests that these tissues are unlikely to be the preferred site of polyomavirus latency, at least in younger children.
Keywords: Adenoids; BK Virus; Carrier State; Child; Child, Preschool; Female; Herpesvirus 6, Human; Humans; Immunocompetence; Italy; JC Virus; Male; Neutrophils; Palatine Tonsil; Polyomavirus Infections; Simian virus 40; Viral Load; Virus Latency